Pro Poor and Community Based Tourism: Case Study of an Investigation into PPT and CBT in Les Village, Bali - weigall, vanessa (2013)
This paper presents the case study of an attempt to introduce tourism as a tool to alleviate poverty in a Balinese village. Despite a positive feasibility study in 2011, tourism has failed to develop. The case study describes the series of events which occurred before, during and after the feasibility study. It then reviews these events in light of themes uncovered during an extensive literature review of Pro-poor and Community-Based Tourism. The study concludes that that the failure to implement tourism can be in large part attributed to a combination of lack of leadership, lack of community participation, and failure to address power imbalances. These have led to disempowerment of the community on multiple levels.